Incidence and Prevalence of Periodontitis among 90 Patients Diagnosed with Salivery Gland Tumor in Duhok City - Dijwar Salih Ibrahim; Hanan Abdulkader Abdullah (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background and Objectives: Globally, there was (20-50) % periodontal disease’s prevalence. This diseaseis one of the tooth loss causes that might be compromising the life quality, self confidence, esthetics, andmastication. The major problem that salivary gland tumors do is decreasing the amount of saliva in theoral cavity that led to change in oral flora and dehydration of the tissue, especially periodontal tissue. Thisstudy was held to found the direct relationship between saliva amount and periodontitis. Methods: Thisepidemiological study was held out by a collection of data from 90 patients that seeking out clinics inDuhok and Zakho and seeking Azadi general hospital complaining from periodontal problems. Results: 90patients involved in this study 47(%52.22) of theme with history of parotid gland tumor, 24(%26.66) withsubmandibular salivary gland tumor, and 19(%21.11 with sublingual salivary gland tumor.68 (75.55%) arebenign category while 22(24.44%) malignant patients having severe xerostomia are 28(31.11%) Moderatetypes of xerostomia are 14(%15.55) patients, while the mild type is 22(24.44%). And those with noxerostomia are 26(28.88%) patients.